Development of the Canadian Spinal Cord Injury Best Practice (Can-SCIP) Guideline: Methods and overview. (30th September 2021) - Patsakos, Eleni M.; Bayley, Mark T.; Kua, Ailene; Cheng, Christiana; Eng, Janice; Ho, Chester; Noonan, Vanessa K.; Querée, Matthew; Craven, B. Catharine; ,
Abstract : Introduction: Spinal cord injury (SCI) is a life-altering injury that leads to a complex constellation of changes in an individual's sensory, motor, and autonomic function which is largely determined by the level and severity of cord impairment. Available SCI-specific clinical practice guidelines (CPG) address specific impairments, health conditions or a segment of the care continuum, however, fail to address all the important clinical questions arising throughout an individual's care journey. To address this gap, an interprofessional panel of experts in SCI convened to develop the Canadian Spinal Cord Injury Best Practice (Can-SCIP) Guideline. This article provides an overview of the methods underpinning the Can-SCIP Guideline process. Methods: The Can-SCIP Guideline was developed using the Guidelines Adaptation Cycle. A comprehensive search for existing SCI-specific CPGs was conducted. The quality of eligible CPGs was evaluated using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument. An expert panel ( n = 52) convened, and groups of relevant experts met to review and recommend adoption or refinement of existing recommendations or develop new recommendations based on evidence from systematic reviews conducted by the Spinal Cord Injury Research Evidence (SCIRE) team. The expert panel voted to approve selected recommendations using an online survey tool. Results: The Can-SCIP Guideline includes 585 total recommendations from 41 guidelines, 96 recommendations that pertain to the Components of the Ideal SCI Care System section, and 489 recommendations that pertain to the Management of Secondary Health Conditions section. Most recommendations ( n = 281, 48%) were adopted from existing guidelines without revision, 215 (36.8%) recommendations were revised for application in a Canadian context, and 89 recommendations (15.2%) were created de novo . Conclusion: The Can-SCIP Guideline is the first living comprehensive guideline for adults with SCI in Canada across the care continuum.